Biogeographic Patterns of South American Anurans - Vasconcelos, Tiago S. [UNESP]; Da Silva, Fernando R.; Dos Santos, Tiago G.; Prado, Vitor H. M.; Provete, Diogo B. (Springer Nature, 2019)
This book analyzes different facets of anuran amphibian distribution in South America. We integrate alternative biological metrics employing cutting-edge methods to understand the dynamic processes underlying species distribution patterns. By using the modern biogeographic toolbox, we explore how richness gradients, phylogenetic diversity, functional diversity, and range size/endemism distribution of amphibians vary along the continent. Moreover, we present a robust proposal for priority areas for conservation of anurans in South America that maximizes representativeness of distinct biodiversity facets.
Keywords: amphibian distribution patterns; amphibians in South America; biogeography of amphibians; conservation of amphibians in South America; macroecology of amphibians